Mortality after surgery with SARS-CoV-2 infection in England: a population-wide epidemiological study. (August 2021) - Abbott, T.E.F.; Fowler, A.J.; Dobbs, T.D.; Gibson, J.; Shahid, T.; Dias, P.; Akbari, A.; Whitaker, I.S.; Pearse, R.M.
Abstract: Background: The COVID-19 pandemic has heavily impacted elective and emergency surgery around the world. We aimed to confirm the incidence of perioperative severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and associated mortality after surgery. Methods: Analysis of routine electronic health record data from NHS hospitals in England. We extracted data from Hospital Episode Statistics in England describing adult patients undergoing surgery between January 1, 2020 and February 28, 2021. The exposure was SARS-CoV-2 infection defined by International Classification of Diseases (ICD)-10 codes. The primary outcome measure was 90 day in-hospital mortality. Data were analysed using multivariable logistic regression adjusted for age, sex, Charlson Comorbidity Index, Index of Multiple Deprivation, presence of cancer, surgical procedure type and admission acuity. Results are presented as n (%) and odds ratios (OR) with 95% confidence intervals (CI). Results: We identified 2 666 978 patients undergoing surgery of whom 28 777 (1.1%) had SARS-CoV-2 infection. In total, 26 364 (1.0%) patients died in hospital. SARS-CoV-2 infection was associated with a much greater risk of death (SARS-CoV-2: 6153/28 777 [21.4%] vs no SARS-CoV-2: 20 211/2 638 201 [0.8%]; OR=5.7 [95% CI, 5.5–5.9]; P <0.001). Amongst patients undergoing elective surgery, 2412/1 857 586 (0.1%) had SARS-CoV-2, of whom 172/2412 (7.1%) died, compared with 1414/1 857 586 (0.1%) patients without SARS-CoV-2 (OR=25.8 [95% CI, 21.7–30.9]; P <0.001). Amongst patients undergoing emergency surgery, 22 918/582 292 (3.9%) patients had SARS-CoV-2, of whom 5752/22 918 (25.1%) died, compared with 18 060/559 374 (3.4%) patients without SARS-CoV-2 (OR=5.5 [95% CI, 5.3–5.7]; P <0.001). Conclusions: The low incidence of SARS-CoV-2 infection in NHS surgical pathways suggests current infection prevention and control policies are highly effective. However, the high mortality amongst patients with SARS-CoV-2 suggests these precautions cannot be safely relaxed.